Inside Back Cover: 2H and 139La NMR Spectroscopy in Aqueous Solutions at Geochemical Pressures (Angew. Chem. Int. Ed. 51/2015). Issue 51 (26th October 2015) - Ochoa, Gerardo; Pilgrim, Corey D.; Martin, Michele N.; Colla, Christopher A.; Klavins, Peter; Augustine, Matthew P.; Casey, William H.
Abstract : A high‐pressure NMR probe head that can attain pressures up to 2.0 GPa is used for the study of an aqueous solution of LaCl3 . In their Communication on page 15444 ff., W. H. Casey et al. show that a ruby sphere coupled to a fiber‐optic cable allows pressure estimates with an improved electrical feedthrough design for an established high‐pressure NMR probe. Spin–lattice relaxation rates are reported as a function of pressure and concentration.